Liberal or radical? - Bergman, Tabe (Javnost (Ljubljana), 2013)
What James Curran calls the liberal meta-narrative of media history is the standard framework employed in describing the trajectory of the Dutch media. Yet much evidence indicates that throughout the twentieth century the Dutch media have more commonly served elite interests than the public interest. Initially the media were subservient to politics, later the market became dominant. This paper criticises the liberal reading of Dutch media history and argues for the viability of a radical reading. After a review of historiographical issues, a critical history of the Dutch media from the thirties onwards is presented, with a focus on the period since the sixties.
Keywords: Nizozemska; mass media; množični mediji; zgodovinski pregledi; 20.st.